GE_GERICHTE C/443/2013 vom 4. November 2016 - GE Cour de justice (2016)
DIVORCE; OBLIGATION D'ENTRETIEN; CONJOINT; MAJORITÉ(ÂGE); ENFANT; RÉGIME MATRIMONIAL; ACQUÊT; PRÉVOYANCE INDIVIDUELLE; IMMEUBLE | CC.125; CC.205; CC.211; CC.285